Rationale, design and conduct of a comprehensive evaluation of a primary care based intervention to improve the quality of life of osteoarthritis patients. The PraxArt-project: a cluster randomized controlled trial [ISRCTN87252339] - Muth Christiane; Gensichen Jochen; Wensing Michel; Körner Thorsten; Rosemann Thomas; Joos Stefanie; Szecsenyi Joachim (BMC, 2005)
Abstract Background Osteoarthritis (OA) has a high prevalence in primary care. Conservative, guideline orientated approaches aiming at improving pain treatment and increasing physical activity, have been proven to be effective in several contexts outside the primary care setting, as for instance the Arthritis Self management Programs (ASMPs). But it remains unclear if these comprehensive evidence based approaches can improve patients' quality of life if they are provided in a primary care setting. Methods/Design PraxArt is a cluster randomised controlled trial with GPs as the unit of randomisation. The aim of the study is to evaluate the impact of a comprehensive evidence based medical education of GPs on individual care and patients' quality of life. 75 GPs were randomised either to intervention group I or II or to a control group. Each GP will include 15 patients suffering from osteoarthritis according to the criteria of ACR. In intervention group I GPs will receive medical education and patient education leaflets including a physical exercise program. In intervention group II the same is provided, but in addition a practice nurse will be trained to monitor via monthly telephone calls adherence to GPs prescriptions and advices and ask about increasing pain and possible side effects of medication. In the control group no intervention will be applied at all. Main outcome measurement for patients' QoL is the GERMAN-AIMS2-SF questionnaire. In addition data about patients' satisfaction (using a modified EUROPEP-tool), medication, health care utilization, comorbidity, physical activity and depression (using PHQ-9) will be retrieved. Measurements (pre data collection) will take place in months I-III, starting in June 2005. Post data collection will be performed after 6 months. Discussion Despite the high prevalence and increasing incidence, comprehensive and evidence based treatment approaches for OA in a primary care setting are neither established nor evaluated in Germany. If the evaluation of the presented approach reveals a clear benefit it is planned to provide this GP-centred interventions on a much larger scale.